Evaluation of Changes in Workload and Feasibility of Meeting TPG Requirements at SMK Bogor Barat After Permendikdasmen 11/2025 - Ani Nuryani; Mohamad Deni; Ani Rahmiyati; Helni Ekasari (Publikasi Indonesia, 2025)
The regulation introduces a flexible workload system, recognizing additional tasks beyond face-to-face teaching hours and addressing challenges faced by vocational teachers in meeting previous requirements. The research aims to analyze changes in workload feasibility, teacher perceptions, and institutional factors influencing TPG fulfilment. This research evaluates teacher workload changes and how they affect eligibility for the Teacher Professional Allowance (TPG) at Vocational High Schools (SMK) in the Bogor Barat region after the implementation of the Ministry of Education and Culture Regulation No. 11 of 2025. The regulation introduces significant changes to the minimum workload and distribution of teaching hours, which directly influence teachers' rights to the TPG. This research uses a quantitative descriptive approach, collecting primary data through questionnaires and documentation of teachers' workloads before and after the regulation was enacted. The analysis shows a decline in teachers independently meeting the minimum teaching hours of 24 JP/week, especially in vocational subjects with reduced hours. Consequently, some teachers had to increase their hours by working across schools or taking on additional administrative tasks to retain their eligibility for TPG. This research recommends that the government regularly evaluate the policy and allow flexibility in setting workloads for vocational teachers to prevent their professional rights from being compromised.